2021
DOI: 10.3390/su13084101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Employee Learning, Knowledge, Benefits, and Satisfaction on Employee Performance and Career Growth in the Hospitality Industry

Abstract: The service industry is considered one of the fastest growing industries in the world, especially in the context of developing countries with economies which rely on tourism sectors as the drivers for economic growth. The development of human resources can directly support the expansion of this industry. The aim of the current study was to investigate the relationships among factors at the employee level, including employee learning and knowledge. Furthermore, this study aimed to analyze the relationships amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
1
22
0
9
Order By: Relevance
“…Employee learning, as defined by Yoopetch et al (2021), is a continuous process that takes place while employees are performing their tasks and responsibilities in their job descriptions and beyond. It can happen through everyday work activities or through more formal, externally led competence development programs.…”
Section: Conceptual Model: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Employee learning, as defined by Yoopetch et al (2021), is a continuous process that takes place while employees are performing their tasks and responsibilities in their job descriptions and beyond. It can happen through everyday work activities or through more formal, externally led competence development programs.…”
Section: Conceptual Model: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Employees are encouraged and rewarded in a learning organization for acquiring, creating, and sharing knowledge with others. Employee learning refers to the ongoing process of acquiring knowledge and skills while performing job tasks and responsibilities (Yoopetch et al, 2021). When employees interact, they should embrace change, adapt to change, and be prepared to acknowledge change (Zamir, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Generation Z (centennials) refers to the generation that was born between 1997 and 2012, following millennials (Gabriel et al, 2020). Yoopetch et al (2021) indicated that employee learning is an influential factor for employee performance, and found that the former must be an important consideration for organizations. Shatto and Erwin (2017) explain higher education institutions must reimagine and reengineer the learning ecosystem of Gen Z, as this generation has learning preferences and different learning abilities from the other generations.…”
Section: The Learning Abilities Of Millennials and Generation Zmentioning
confidence: 99%
“…Yoopetch et al . (2021) indicated that employee learning is an influential factor for employee performance, and found that the former must be an important consideration for organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although we argue that the distal relationship between students’ future orientation and their perceived employability is mediated by problem-based learning, we expect a moderating effect on this relationship following career construction theory, i.e., some career-related resources (e.g., personal factors) may act as a booster to strengthen the association between predictors and career outcomes. Among these personal-related resources, scholars have suggested that individuals’ knowledge and skills resources function as their career-oriented assets, facilitating their career development (Yoopetch et al, 2021 ) Thus, in this section, based on career construction theory, we explore how two important characteristics of students—job market knowledge and proactive personality—moderate the influence of students’ future orientation on their perceived employability via problem-based learning.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%